The effects of autobiographical memory flexibility (MemFlex) training: An uncontrolled trial in individuals in remission from depression. (September 2016) - Hitchcock, Caitlin; Mueller, Viola; Hammond, Emily; Rees, Catrin; Werner-Seidler, Aliza; Dalgleish, Tim
Abstract: Background and Objectives: Impaired cognitive processing is a key feature of depression. Biases in autobiographical memory retrieval (in favour of negative and over-general memories) directly impact depression symptoms, but also influence downstream cognitive factors implicated in the onset and maintenance of the disorder. We introduce a novel cognitive intervention, MemFlex, which aims to correct these biases in memory retrieval and thereby modify key downstream cognitive risk and maintenance factors: rumination, impaired problem solving, and cognitive avoidance. Method: Thirty eight adults with remitted Major Depressive Disorder completed MemFlex in an uncontrolled clinical trial. This involved an orientation session, followed by self-guided completion of six workbook-based sessions over one-month. Assessments of cognitive performance and depression symptoms were completed at pre- and post-intervention. Results: Results demonstrated medium-sized effects of MemFlex in improving memory specificity and problem solving, and decreasing rumination, and a small effect in reducing cognitive avoidance. No significant change was observed in residual symptoms of depression. Limitations: This study was an uncontrolled trial, and has provided initial evidence to support a larger-scale, randomized controlled trial. Conclusions: These findings provide promising evidence for MemFlex as a cost-effective, low-intensity option for reducing cognitive risk associated with depression. Highlights: We completed an uncontrolled trial of an autobiographical memory training programme. Memory specificity and problem solving improved from pre- to post-intervention. Rumination and cognitive avoidance decreased from pre- to post-intervention. No change was observed in residual depression symptoms. Memory flexibility training is a promising option for reducing depressive risk.